2013
DOI: 10.1097/bpo.0b013e3182746bc1
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Nerve IX and X Impairment After a Sports-related Jefferson (C1) Fracture in a 16-Year-Old Male

Abstract: Level V, case report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Videofluoroscopic swallowing studies were the most commonly used instrumental assessment, however FEES was used in conjunction with VFSS in two studies [11, 13]. Synthesis of the results from the 5 studies revealed a common pattern of swallowing difficulties for individuals with spinal cord injury; these results are summarized in Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Videofluoroscopic swallowing studies were the most commonly used instrumental assessment, however FEES was used in conjunction with VFSS in two studies [11, 13]. Synthesis of the results from the 5 studies revealed a common pattern of swallowing difficulties for individuals with spinal cord injury; these results are summarized in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…As these complications can impair swallowing function, and lead to secondary restrictions of pharyngeal movement or epiglottic deflection, the use of steroid treatment or antibiotics post-operatively has potential to improve swallowing outcomes [23, 24]. In the studies reviewed, steroids and antibiotics appeared to contribute to improved swallowing function when used in addition to other swallowing interventions, primarily tube feedings [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Injury to the four lower cranial nerves IX, X, XI and XII, eponymously named Collet‐Sicard Syndrome, is reported in 14 cases of blunt cranial trauma . Other reported cases of unilateral vagus nerve paralysis secondary to trauma involve combinations of two or more of the lower cranial nerves . Axial loading is the most common mechanism of injury and in all except one case a fracture of the occipital condyle or C1 vertebra is described.…”
mentioning
confidence: 99%